2022
DOI: 10.1227/neu.0000000000002260
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intraoperative Rapid Molecular Diagnosis in Precision Surgery for Glioma: Mimic the World Health Organization CNS5 Integrated Diagnosis

Abstract: BACKGROUND:With the advent of the molecular era, the diagnosis and treatment systems of glioma have also changed. A single histological type cannot be used for prognosis grade. Only by combining molecular diagnosis can precision medicine be realized.OBJECTIVE:To develop an automatic integrated gene detection system (AIGS) for intraoperative detection in glioma and to explore its positive role in intraoperative diagnosis and treatment.METHODS:We analyzed the isocitrate dehydrogenase 1 (IDH1) mutation status of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…In the preliminary study (Chinese Clinical Trial Registry: ChiCTR2100048172), we have evaluated the sensitivity, specificity, and accuracy of the detection technology, and the detection results are completely consistent with the results of the NGS. It can complete the automatic interpretation of the results within 1 h, and the accuracy rate is up to 100%,which can be applied in the operation ( Xue et al, 2022 ). In our case, it is precisely because of the TERTp mutation information provided by AIGS that we can diagnose WHO grade 3 meningioma during operation.…”
Section: Discussionmentioning
confidence: 99%
“…In the preliminary study (Chinese Clinical Trial Registry: ChiCTR2100048172), we have evaluated the sensitivity, specificity, and accuracy of the detection technology, and the detection results are completely consistent with the results of the NGS. It can complete the automatic interpretation of the results within 1 h, and the accuracy rate is up to 100%,which can be applied in the operation ( Xue et al, 2022 ). In our case, it is precisely because of the TERTp mutation information provided by AIGS that we can diagnose WHO grade 3 meningioma during operation.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that, while only 12% of glioma patients carry the IDH mutation, discovered after genomic analysis, those with the IDH mutation tend to have a more favorable survival prognosis. Raman analysis reveals distinctive differences in the spectral features of scattered light from various cellular components, including lipids, collagen, DNA, cholesterol, and phospholipids [ 99 , 100 ]. Notably, a study involving 38 unprocessed samples, comprising a total of 2073 Raman spectra, demonstrated the potential of RS to differentiate between IDH-mutant (IDH-MUT) and IDH-wildtype (IDH-WT) gliomas with an accuracy and precision of 87%.…”
Section: Diagnostic Toolsmentioning
confidence: 99%
“…Reagents for nucleic acid purification and qRT-PCR amplification were placed in the cartridges in advance, as reported by Hao Xue et al AIGS real-time fluorescence integrates nucleic acid extraction and real-time gene amplification detection, and achieves a fully closed automatic output from samples to genes in the form of a microfluidic card slot. Compared with next-generation sequencing, AIGS has high accuracy in showing results and is a quick and accurate methodology for providing molecular information during surgery [8].…”
Section: Idhmentioning
confidence: 99%